Peralihan Hak Atas Tanah Dengan Perjanjian Jual Beli Menurut Hukum Pertanahan Indonesia - Ayu Larasati; Raffles Raffles (Zaaken: Journal of Civil and Business Law, 2020)
This article talks about the legal arrangements regarding the transfer of land rights through the sale and purchase of land for land that has not been registered; and legal consequences of the transfer of land rights because it is not registered at the Land Office in terms of Government Regulation concerning Land Registration. The research method used is the normative legal research method and the approach used is the statutory approach and the conceptual approach ). The results of the study show that, first, the legal arrangements regarding the transfer of land rights through the sale and purchase of land for land that has not been registered, the transfer of rights to land due to the sale and purchase of land that has not been registered or in other words uncertified land rights in the provisions of Government Regulation concerning Land Registration can be sold / transferred ownership rights with the main requirement that the seller is able to show proof of ownership of land such as a previous sale and purchase letter (seal letter), kekitir / petok / girik, statement of the village head / local official, which explains the truth about ownership of the land owner. Second, the legal consequences of the transfer of land rights because they are not registered at the Land Office in terms of Government Regulation concerning Land Registration are legal according to the law if the transfer of land rights due to the sale and purchase of land that has not been registered already meets the material purchase requirements, namely "Light and “Cash". Keywords: Transfer of Land Rights; Sale and Purchase of Land. Abstrak Artikel ini berbicara mengenai pengaturan hukum mengenai peralihan hak atas tanah melalui jual beli tanah terhadap tanah yang belum didaftarkan; dan akibat hukum peralihan hak atas tanah karena tidak terdaftar di Kantor Pertanahan ditinjau dari Peraturan Pemerintah tentang Pendaftaran Tanah.Metode penelitian yang digunakan adalah metode penelitian hukum normatif dan pendekatan yang digunakan adalah pendekatan perundang-undangan (normative approach) dan pendekatan konseptual (conceptual approach). Hasil penelitian menunjukkan bahwa pertama, pengaturan hukum mengenai peralihan hak atas tanah melalui jual beli tanah terhadap tanah yang belum didaftarkan bahwa peralihan hak atas tanah karena jual beli terhadap tanah yang belum didaftarkan atau dengan kata lain tanah hak yang tidak bersertifikat dalam ketentuan Peraturan Pemerintah tentang Pendaftaran Tanah dapat dijual/dialihkan hak kepemilikannya dengan syarat utama bahwa penjual mampu menunjukkan bukti-buktikepemilikan tanah seperti surat jual beli sebelumnya (surat segel), kekitir/petok/girik, keterangan kepala desa/pejabat setempat, yang menerangkan kebenaran mengenai pemilikan dari pemilik tanah. Kedua, adapun akibat hukum peralihan hak atas tanah karena tidak terdaftar di Kantor Pertanahan ditinjau dari Peraturan Pemerintah tentang Pendaftaran Tanah adalah sah menurut hukum apabila peralihan hak atas tanah karena jual beli terhadap tanah yang belum didaftarkan tersebut sudah memenuhi syarat materil jual beli yaitu “Terang dan“Tunai”. Kata Kunci: Peralihan Hak Atas Tanah; Jual Beli Tanah.